Technostress : coping with technology @ work @ home @ play - Weil, Michelle M. (John Wiley New YorkUS, 1997)
Examines the social and psychological aspects of technostress. Seeks to help victims to overcome accompanying feelings such as: frustration, inadequacy, and intimidation; and take action to master the technology. Suggests 5 steps to ending societal technostress.\n \n